Pengaruh Penggunaa Media E – Learning Quipper School Terhadap Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Kelas X Di SMA Muhammadiyah I UNISMUH Makassar - Muh. Noer Ghaffar Herman; Maryam; Mursyid Fikri (Advances In Education Journal, 2025)
This study aims to determine the effect of using the e-learning platform Quipper School on improving students’ learning outcomes in Islamic Religious Education (PAI) for Grade X students at SMA Muhammadiyah I Unismuh Makassar. The research problem is formulated as follows: (1) How is the use of Quipper School e-learning media in Islamic Religious Education? (2) How are the students’ learning outcomes in Islamic Religious Education? (3) Is there any influence of using Quipper School e-learning media on the improvement of students’ learning outcomes?This research employed a quantitative approach with a descriptive quantitative method. Data were collected through observation, documentation, and questionnaires. The population consisted of all Grade X students at SMA Muhammadiyah I Unismuh Makassar, with the sample selected using purposive sampling.The results of the study indicate that the use of Quipper School e-learning media falls into the “good” category. Students’ learning outcomes also showed a significant improvement after using the platform. Based on statistical tests, it was found that there is a positive and significant effect of using Quipper School on enhancing students’ learning outcomes in Islamic Religious Education.